Indonesia's Position as a Rule of Law Based on Pancasila - Entah, Aloysius R (Law Research Review Quarterly, 2016)
A rule of law is a state that stands on a legal basis to regulate the life of the nation and state. In state theory and practice, we recognize the concept of the rule of law "Rechtstaat", the concept of the rule of law "Rule of Law", the concept of the rule of law "Religy Legality" and "Islamic Nomocracy", the concept of the rule of law "Socialist Legality", and for the Unitary Republic of the Republic Indonesia rests on the concept of "a rule of law based on Pancasila"